2018
DOI: 10.2478/pjen-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Host-age effects and the efficiency of the pupal parasitoid Dirhinus giffardii (Silvestri, 1913) (Hymenoptera: Chalcididae) against the melon fly Bactrocera cucurbitae (Coquillett, 1849) (Diptera: Tephritidae)

Abstract: Dirhinus giffardii is an efficient and aggressive pupal parasitoid of tephritid flies, including Bactrocera cucurbitae. Here we report on the various biological aspects of Dirhinus giffardii, mainly host-age preference, potential as well as the survival of this parasitoid from the pupae of different ages and its in vivo release against Bactrocera cucurbitae. The emergence rate of parasitoids was higher in old pupae than in fresh pupae. Similarly, the lifespan and potential of parasitoids emerged from older pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Liu et al (2016) reported that S. endius can cause 80% kill of melon fly pupae under laboratory conditions. Mehmood et al (2018) found that D. giffardii when reared on older pupae of melon fly effectively declined melon fly population under greenhouse environment.…”
Section: Biological Control Agents Against Melon Fruit Flymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2016) reported that S. endius can cause 80% kill of melon fly pupae under laboratory conditions. Mehmood et al (2018) found that D. giffardii when reared on older pupae of melon fly effectively declined melon fly population under greenhouse environment.…”
Section: Biological Control Agents Against Melon Fruit Flymentioning
confidence: 99%
“…In addition to mortality, fungal pathogen infections can modify behaviour and reduce mating competitiveness and attractiveness of the fruit fly (Dimbi et al, 2013). Thaochan and Ngampongsai (2015) evaluated TA B L E 1 Parasitoids of Z. cucurbitae Parasitoid Host stage References Psyttalia fletcheri (=Opius fletcheri) Larval and pupal stages Narayanan and Chawla (1962), Chinajariyawong et al (2000), Ramadan and Messing (2003), Stibick (2004), Vargas et al (2004), Vargas et al (2012)Fopius arisanus (=Opius oophilus) Egg, larval and pupal stagesRamadan and Messing (2003),Bautista et al (2004),Stibick (2004),Vargas et al (2004) Spalangia endius (=Spalangia stomoxysiae, Spalangia philippinensis)Pupal stageNarayanan and Chawla (1962),Stibick (2004),Tang et al (2015),Liu et al (2016),Li et al (2021) Dirhinus giffardii Pupal stageNishida (1955),Narayanan and Chawla (1962),Naveed et al (2014),Mehmood et al (2018) Pachycrepoideus vindemmiae (=Pachycrepoideus dubius)Pupal stageNarayanan and Chawla (1962),Zhao et al (2013)…”
mentioning
confidence: 99%
“…Our findings were concurrent with those of B. zonata and B. cucurbitae which showed increased amount of parasitism as the host pupae age advanced, showing peak parasitism on pupae of at the age of 3 days and a subsequent decline (Naveed et al, 2014). It was also suggested that a greater potential regarding fecundity, parasitism performance and survival is achieved when parasitoids reared on older pupae of B. cucurbitae, as these parasitoids have been found to efficiently suppress B. cucurbitae populations in greenhouse (Mehmood et al, 2018). Likewise, older puparia for oviposition are also preferred by some other parasitoid wasps while having other choices (Tang et al, 2015).…”
Section: Correlation Between Percent Of B Dorsalis Pupae Parasitized ...mentioning
confidence: 99%